Implementasi Metode Technique For Order By Similarity To Ideal Solution (Topsis) Dalam Sistem Pendukung Keputusan Kelayakan Penerimaan Kredit - I Putu Eka Sudarsana (JURNAL AKADEMISI VOKASI, 2024)
The objective of this study is to apply a Decision Support System approach to evaluate and suggest business credit approval at Tani Karya Sejahtera Cooperative. Technique for Order by Similarity to Ideal Solution (TOPSIS) is the name of this approach. Five criteria are used in this research: Building Land Tax (PBB), Income, Guarantee, Business Establishment Permit (SIUP), and Loan Application Form (FPP). In addition to applying the Topsis approach, method testing was done. This seeks to determine the most relevant/appropriate approach to assessment-taking. The accuracy of debtor rankings is tested using the MAP approach as part of the testing procedure. Using the top 10 ranking data, the MAP methodology was used to assess the TOPSIS method's implementation. The test results indicated that the TOPSIS method was a method with good accuracy, with a MAP test value of 66%. Since the TOPSIS method demonstrated a fairly high degree of accuracy in this study, it is believed that more research will be able to refine the approach.